Design, microfabrication, and characterization of a moulded PDMS/SU-8 inkjet dispenser for a Lab-on-a-Printer platform technology with disposable microfluidic chip. Issue 17 (22nd July 2016) - Bsoul, Anas; Pan, Sheng; Cretu, Edmond; Stoeber, Boris; Walus, Konrad
Abstract : A disposable inkjet dispenser is developed and integrated with microfluidics to demonstrate a Lab-on-a-Printer enabling on-the-fly manipulation of printed materials. Abstract : In this paper, we present a disposable inkjet dispenser platform technology and demonstrate the Lab-on-a-Printer concept, an extension of the ubiquitous Lab-on-a-Chip concept, whereby microfluidic modules are directly integrated into the printhead. The concept is demonstrated here through the integration of an inkjet dispenser and a microfluidic mixer enabling control over droplet composition from a single nozzle in real-time during printing. The inkjet dispenser is based on a modular design platform that enables the low-cost microfluidic component and the more expensive actuation unit to be easily separated, allowing for the optional disposal of the former and reuse of the latter. To limit satellite droplet formation, a hydrophobic-coated and tapered micronozzle was microfabricated and integrated with the fluidics to realize the dispenser. The microfabricated devices generated droplets with diameters ranging from 150–220 μm, depending mainly on the orifice diameter, with printing rates up to 8000 droplets per second. The inkjet dispenser is capable of dispensing materials with a viscosity up to ∼19 mPa s. As a demonstration of the inkjet dispenser function and application, we have printed type I collagen seeded with human liver carcinoma cells (cell line HepG2), to form patterned biological structures.